Behavioral Self‐Regulation, Early Academic Achievement, and the Effectiveness of Urban Schools for Low‐Income Ethnic Minority Children. Issue 3 (31st March 2018) - Caughy, Margaret O.; Mills, Britain; Brinkley, Dawn; Owen, Margaret T.
Abstract: The independent and joint associations between child behavioral self‐regulation ability and school effectiveness in relation to academic achievement were examined in a sample of low‐income African American ( n =  132) and Latino ( n =  198) children attending kindergarten and first grade across a large metropolitan area. Child behavioral self‐regulation and school effectiveness were positively associated with both reading and mathematics performance. School effectiveness moderated the effect of behavioral self‐regulation on reading but not math achievement. Lower child behavioral self‐regulation during early elementary school was associated with lower reading achievement the following year but only among children attending less effective schools. Behavioral self‐regulation was not related to reading achievement among children attending more effective schools. Implications of these findings for policies addressing disparities in early academic achievement are discussed. Highlights: Behavioral self‐regulation is associated with better achievement for low‐income minority children. Urban school quality is important for early academic achievement. School quality is more important for children with poor behavioral self‐regulation at school entry.